AUTOMATIC GENERATION OF ANCIENT POTTERY PROFILES USING CAD SOFTWARE - Ionut Badiu; Zsolt Buna; Radu Comes (Journal of Ancient History and Archaeology, 2015)
The paper presents a new approach for the virtual reconstruction of historical artifacts such as ceramic pots. The technique is based on the photogrammetry method through which the profile line of the pot is achieved and which is composed by a fixed number of inflection points. The parameterization of the profile is then followed by the creation of a macro (script) in CAD software in order to automatically generate the shape of the ceramic pot. The case study included in the article consists of a total of 15 families of ancient ceramic pottery. The purpose of this technique is to serve as a support both for historians, archaeologists and restorers, as well as for students who desire a fast, fair and accessible virtual reconstruction of ceramic pots, regardless of their considered knowledge in designing or editing a programming language.